The Meaning of Entrepreneurship: A Modular Concept - Michael Peneder (Austrian Institute of Economic Research (WIFO), 2009)
Entrepreneurship has been characterised as one of the most intriguing but equally elusive concepts in economics. This critical review first surveys its major intellectual roots and then proposes a modular concept of entrepreneurship that preserves its essentially distinctive behavioural, functional, and occupational dimensions. It argues that the behavioural definition identifies the only attribute that is both comprehensive and unique to the nature of entrepreneurship, while the functional and occupational definitions add what is specificity required for many analytical purposes. To validate the concept, the paper discusses the appropriate empirical units of observation and maps a general policy framework.
Keywords: 330; Entrepreneurship; market co-ordination; innovation; technology diffusion; occupational choice; Entrepreneurship-Ansatz; Unternehmensgründung; Technischer Fortschritt; Innovationsdiffusion; Berufswahl; Ökonomische Ideengeschichte; Theorie